Scientifi c assessment of the correspondence of Santiago Ramón y Cajal (1852-1934). A view at the history of the neuroscience - Lopera Chaves, Marta Cecilia (Pensando Psicología, 2010)
This article describes the results of research whose main objective was to determine how important scientifi c correspondence and what role he played in the scientifi c work of Santiago Ramón y Cajal, considered the fi rst neuroscientist of all time. Examined 360 letters exchanged between Cajal and other researchers of his time, we found that played an important role in the establishment of personal and scientific relations between researchers and supported, expanded and complemented the investigative work of Cajal, becomingthe letters as part of his scientifi c Cajal’s Legacy consisting of about 4000 histological preparations, 2000 scientific drawings and over 300 publications.
Keywords: scientifics letters; Cajal’s Legacy; investigative labor; cognitive psychology